Radio imaging of the Subaru/XMM-Newton Deep Field - I. The 100-microJy catalogue, optical identifications, and the nature of the faint radio source population - Simpson, C; Martinez-Sansigre, A; Rawlings, S; Ivison, R; Akiyama, M; Sekiguchi, K; Takata, T; Ueda, Y; Watson, M (2006)
We describe deep radio imaging at 1.4-GHz of the 1.3 square degree Subaru/XMM-Newton Deep Field (SXDF), made with the Very Large Array in B and C configurations. We present a radio map of the entire field, and a catalogue of 505 sources covering 0.8 square degrees to a peak flux density limit of 100 microJy. Robust optical identifications are provided for 90% of the sources, and suggested IDs are presented for all but 14 (of which 7 are optically blank, and 7 are close to bright contaminating objects). We show that the optical properties of the radio sources do not change with flux density, suggesting that AGNs continue to contribute significantly at faint flux densities. We test this assertion by cross-correlating our radio catalogue with the X-ray source catalogue and conclude that radio-quiet AGNs become a significant population at flux densities below 300 microJy, and may dominate the population responsible for the flattening of the radio source counts if a significant fraction of them are Compton-thick.